(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2023)
In the present work, it was investigated about virtual wallets, if they are a viable financial instrument to replace traditional means of payment and if they favor financial inclusion. For this, different points were analyzed. In the first place, key concepts are described to be able to understand the topic analyzed throughout the work, such as virtual wallets, financial inclusion and the SWOT matrix. Second, an in-depth analysis of the existing virtual wallets in the country, the means of payment most used by the population and financial inclusion was carried out. Third, the survey conducted by the researcher was analyzed, establishing relationships between different issues, linked to virtual wallets and financial inclusion. Finally, from the realization of this work, it was possible to understand that Argentina has a favorable scenario to achieve in the future the total banking of the population and to increase the use of virtual wallets.